Airline networks, mergers, and consumer welfare - Kai Hüschelrath; Kathrin Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
We study the consumer welfare effects of mergers in airline networks. Based on the development of a general classification of affected routes, we apply a difference-indifferences approach to exemplarily investigate the price effects of the America West Airlines - US Airways merger completed in 2005. We find that although average prices increased substantially on routes in which both airlines competed either on a non-stop or one-stop basis prior to the merger, substantial average price reductions observed for routes without any premerger overlap suggest that the merger led to a net increase in consumer welfare.
urn:nbn:de:bsz:180-madoc-337141
Keywords: L40; L93; 330; Airline industry; merger; market power; consumer welfare; price effects